2019
DOI: 10.1186/s12978-019-0686-9
|View full text |Cite
|
Sign up to set email alerts
|

Contraception in adolescence: the influence of parity and marital status on contraceptive use in 73 low-and middle-income countries

Abstract: Background There is still a large gap in relation to effectively meet the contraceptive needs and family planning goals of adolescents. Our aim was to describe how having a partner and children impact on contraceptive behavior of sexually active female adolescents from low and middle-income countries (LMICs). Methods Analyses were based on the most recent Demographic and Health Surveys and Multiple Indicator Surveys carried out since 2005 in 73 LMICs with available data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
86
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 30 publications
14
86
4
3
Order By: Relevance
“…Participants who were married and those who were cohabiting were 89% and 57% less likely to use modern contraceptives respectively than their counterparts who were single. In contrast, previous studies among non-refugees adolescents have shown that adolescents who were married were more likely to use modern contraceptives compared to those who were single (25,26). This inconsistency could have been brought about by the difference in setting and study population of the studies compared to ours.…”
Section: Discussioncontrasting
confidence: 75%
“…Participants who were married and those who were cohabiting were 89% and 57% less likely to use modern contraceptives respectively than their counterparts who were single. In contrast, previous studies among non-refugees adolescents have shown that adolescents who were married were more likely to use modern contraceptives compared to those who were single (25,26). This inconsistency could have been brought about by the difference in setting and study population of the studies compared to ours.…”
Section: Discussioncontrasting
confidence: 75%
“…This use of the algorithm is in contrast to the evidence from a study using DHS data from developing countries which identifies striking differences between married and never-married women with regards to unmet need of contraception, and highlights that the youngest (15 to 19 years old) and single have the highest-burden for unmet need (3). Also, a current study in contraceptive behavior among adolescents identifies marital status as a critical factor of contraceptive use (7). Moreover, previous studies estimated that sexually active unmarried women contribute nearly 20% to the overall unmet need in developing countries (5).…”
Section: Introductionmentioning
confidence: 84%
“…However, conceptually, the indicator should consider sexually active women as a denominator regardless of their marital status. Besides, the literature has found that the prevalence of unmet need for contraception varies according to marital status (3,(5)(6)(7). The unmet need can be calculated for sexually active unmarried women when information is available (1,2,6,8,9), such as the case of the Demographic and Health Surveys (DHS) in the Latin American region (9) and in contrast with the situation in national surveys of Asia and North Africa, where surveys do not ask unmarried women about their sexual behavior for cultural reasons (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…et Al in 2016 (36). This could be justi ed with the rigid social norms context, the decision-making capacity and maturity of young women to engage in decision making about their own health care including to opt for modern FP methods since they are more enlightened about the availability of different types of FP method as well as their advantages, compared to younger adolescents who may be naïve (32,36,37).…”
Section: Factors Associated With the Use Of Modern Fp Methodsmentioning
confidence: 99%